Fraudulent Financial Reporting: Fraud Pentagon Analysis In Financial Sector Companies - Agung Prajanto; Lilik Irawati; Imang Dapit Pamungkas (Jurnal Telekomunikasi dan Informatika, 2023)
The purpose of this study is to ascertain how fraudulent financial reporting are detected by fraud pentagon theory. The financial sector companies that listed on the Indonesia Stock Exchange (IDX) in 2019–2021 are the study's population. Purposive sampling is used to determine the sample, leaving 46 companies that satisfy the requirements. Logistic regression is the data analysis technique used in this study. The results indicate that while ineffective monitoring, change in auditor, and change in director had no impact on the fraudulent financial statement, however variables financial stability and number of CEO's picture are significantly influenced fraudulent financial statement.